Related party transactions: Review of the literature - Jopinus Ramli Saragih (Universitas Sebelas Maret, 2021)
Asian financial crisis has led many countries to perform related party transactions, which are transactions made by the firms to affiliated parties and often performed by controlling shareholders. The emergence of related party transactions cannot be separated from the existence of pyramidal ownership, where the controlling shareholder has several layers of ownership. Just as related party transactions can create a conflict of interest between the controller and the minority, the controller may transfer firms’ resources or assets to a parent entity that is not normally listed on a stock exchange. Therefore, in our paper, we would like to discuss about different aspects and arguments on the impact of related party transactions. Prior studies provide various contributions, as one argues that related party transactions are part of an efficient contract, where the two connected parties have better information with each other due to the connection than the unaffiliated parties. On the other hand, several studies suggest that related party transactions have a bad impact and are full of expropriation of minority interests.